Resolving identity-based conflict in nations, organizations, and communities - Rothman, Jay 1958- (The Jossey-Bass conflict resolution series, 1997)
Conflict can either destroy or create - depending on whether and how it is guided. This is the simple yet profound insight that underlies Jay Rothman's innovative new framework for understanding and transforming identity-based conflict. Grounded in his grassroots conflict resolution work in the Middle East - work that earned him the honor of witnessing the historic White House handshake between Prime Minister Yitzhak Rabin and PLO President Yasser Arafat - and brilliantly refined to address a wide range of organizational and community conflicts, Rothman's ARIA model is a versatile and innovative synthesis of the best contemporary ideas in conflict management, resolution, and transformation